Approved and Experimental Small‐Molecule Oncology Kinase Inhibitor Drugs: A Mid‐2016 Overview. Issue 2 (24th October 2016) - Fischer, Peter M.
Abstract: Kinase inhibitor research is a comparatively recent branch of medicinal chemistry and pharmacology and the first small‐molecule kinase inhibitor, imatinib, was approved for clinical use only 15 years ago. Since then, 33 more kinase inhibitor drugs have received regulatory approval for the treatment of a variety of cancers and the volume of reports on the discovery and development of kinase inhibitors has increased to an extent where it is now difficult—even for those working in the field—easily to keep an overview of the compounds that are being developed, as currently there are 231 such compounds, targeting 38 different protein and lipid kinases (not counting isoforms), in clinical use or under clinical investigation. The purpose of this review is thus to provide an overview of the biomedical rationales for the kinases being targeted on the one hand, and the design principles, as well as chemical, pharmacological, pharmaceutical, and toxicological kinase inhibitor properties, on the other hand. Two issues that are especially important in kinase inhibitor research, target selectivity and drug resistance, as well as the underlying structural concepts, are discussed in general terms and in the context of relevant kinases and their inhibitors.